2020
DOI: 10.1074/jbc.ra119.012449
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity between HSP70 paralogs caused by variable interactions with specific co-chaperones

Abstract: Heat shock protein 70 (HSP70) chaperones play a central role in protein quality control and are crucial for many cellular processes, including protein folding, degradation, and disaggregation. Human HSP70s compose a family of 13 members that carry out their functions with the aid of even larger families of co-chaperones. A delicate interplay between HSP70s and co-chaperone recruitment is thought to determine substrate fate, yet it has been generally assumed that all Hsp70 paralogs have similar activities and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 80 publications
3
45
0
2
Order By: Relevance
“…Specifically, the J-domain protein (also referred to as DNAJ) and nuclear exchange factor (NEF) families have been suggested as factors that confer functional diversity to HSPA machines [ 41 , 42 ]. A recent report confirmed that distinct functions of HSPA1 and HSPA1L dependent on the intracellular co-chaperone background and specifically are directed by the differential interaction with preferred nuclear exchange factors (NEFs) [ 8 ].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Specifically, the J-domain protein (also referred to as DNAJ) and nuclear exchange factor (NEF) families have been suggested as factors that confer functional diversity to HSPA machines [ 41 , 42 ]. A recent report confirmed that distinct functions of HSPA1 and HSPA1L dependent on the intracellular co-chaperone background and specifically are directed by the differential interaction with preferred nuclear exchange factors (NEFs) [ 8 ].…”
Section: Discussionmentioning
confidence: 91%
“…Whether the functions of cytoplasmic/nuclear HSPA overlap or differ has not yet been sufficiently recognized [ 5 ]. Although it is generally accepted that their functionality is interchangeable, there is important evidence that particular HSPA paralogs may interact differently with the specific client protein(s) and thus have distinct functional significance [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…We exploited the previously described flow cytometry technique FloIT (Whiten et al, 2016) to screen the capacity of various DNAJB isoforms to suppress Fluc DM inclusion formation. Previous to this, Hsp overexpression screens to identify inhibitors of protein aggregation have typically relied on using traditional bulk-based biochemical analyses, such as the filter trap assay or fluorescence microscopy (Hageman et al, 2010;Kakkar et al, 2016a;Serlidaki et al, 2020). However, when screening many different samples, model systems of protein aggregation in cells (Whiten et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, while increased levels of Hsp70 family members reduced SOD1 aggregation and toxicity in cultured mouse primary motor neurons expressing SOD1 G93A (Bruening et al, 1999 ), this had no impact on either survival or onset of motor symptoms in several SOD1 mutant mouse models, including SOD1 G93A (Liu et al, 2005 ). Interestingly, Serlidaki et al ( 2020 ) have recently demonstrated in cell culture that the effect of Hsp70s on the aggregation of the SOD1 A4V mutant depends on the particular Hsp70 variant, which is overexpressed. While HSPA1A suppresses SOD1 aggregation, its close homolog HSPA1L enhances aggregate formation.…”
Section: The Role Of Chaperones In Prion-like Propagationmentioning
confidence: 99%
“…While HSPA1A suppresses SOD1 aggregation, its close homolog HSPA1L enhances aggregate formation. The differences in client fate seem to result from the fact that Hsp110-type co-chaperones prefer to interact with HSPA1A rather than HSPA1L (Serlidaki et al, 2020 ). More specifically, HSPA1A requires the NEF HSPA4 (APG-2) to inhibit SOD1 aggregation, while the aggregation promoting activity of HSPA1L does not depend on this NEF.…”
Section: The Role Of Chaperones In Prion-like Propagationmentioning
confidence: 99%